“DO-IT-YOURSELF” (DIY) Geointerpretation – Making Geology Simple, Fascinating & Fun - Patrick James (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Why does the earth-quake? When does the land-slide? How do rocks bend and break and what makes lava flow and mountains grow? Geointerpretation activities can explain these fascinating and seemingly incomprehensible global phenomena in simple and fun ways to visitors, tourists and the public. According to renowned interpreter Sam Ham (Ham, 1992), this involves “translating complex technical language and concepts into terms and ideas that people can readily understand”; while “doing it in a way that is entertaining and interesting to people”. Meanwhile almost 2500 years ago, the Chinese philosopher Confucius elegantly confirmed that “if we hear we forget, if we see we remember but if we do we understand”. Geotourism activities within Global Geoparks across the world cater for geotourists who want to know more about how the earth system works, as well as to experience the wonders - (and terrors) - of the natural world. Do-It-Yourself (DIY) geointerpretation activities are simple to design, inexpensive to create and very flexible to deliver to geotourists, anywhere. This hands-on workshop will reveal how geointerpretation is made easy using simple everyday materials. For example, making your own banana benders, broken egg-shell planets and lava sandwiches will demonstrate many geological processes including difficult concepts such as Deep Earth, Deep Impacts and Deep Time. Geointerpretation makes visitor experiences (within Geoparks) more enriching, fulfilling and most importantly fun!.